Nancy Huston: L’exilé linguistique - Alves, Ana M. (2019)
Our article proposes an approach to the figure of Nancy Huston as frontier writer. We analyse the representation of the Hustonian exile with a translinguistic and transcultural vision, recalling that for most writers Exile is a rupture, an experience to which they will later testify in their writings because the act of witnessing, experiencing “this silence of exile is inseparable from the attempt to understand, while being aware that it means entering a shadow zone that can never be fully illuminated”1. Through the crossing of cultures, and through the crossing of borders, we try to highlight the relationship of the writer with the mother tongue and the language of exile (adoption), proposing a reflection on the experience of the expatriate in search of milestones.Through the analysis of Lost North and the Lettres parisiennes, we aim to uncover thinking behind “becoming a writer” while questioning the singularity of a transboundary bridge work.